Analisis Penerapan Media Pembelajaran EASY COA dan Pengaruhnya Terhadap Habits of Mind Mahasiswa Jurusan Akuntansi - Mulyanti, Khairaningrum; Tanjung, Riani; Fauzan, Mohamad Nurkamal (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2022)
Learning media is one of the components that affect the learning process, achieve learning goals, and at the end can form the habits of thinking (habits of mind) student. The purpose of this research is to find out how the use of EASY COA affects the habits of Mind students majoring in Accounting. The research method used is causal associative. Data collection using the results of questionnaires distributed to 85 students majoring in Accounting Polytechnic Pos Indonesia who learn Accounting Practicum courses. After the instrument test in the form of validity and reliability, the data is processed and then analyzed with theÂ  test. The results showed EASY COA had a significant positive effect on Habits of Mind with the influence value of 46.6%. Based on hypothesis testing it was concluded that EASY COA fulfil the characteristics as a good learning medium and can improve the habits of mind of accounting students. From these results it is also suggested to developing other android-based accounting learning media.